Daylight performance analysis of TiO2@W-VO2 thermochromic smart glazing in office buildings. (December 2020) - Salamati, Mohammad; Mathur, Pegah; Kamyabjou, Ghazal; Taghizade, Katayoun
Abstract: Thermochromic glazing (TC) is able to modulate the solar radiation transmittance through windows in response to temperature, passively. Apart from the significant role of TC windows in thermal energy conservation in buildings, they affect the indoor daylight performance due to their lower visible transmittance rate and tinted appearance. In this paper, we carried out a comprehensive study on the impact of TiO2@W-VO2 thermochromic glazing, fabricated by the authors, on indoor daylighting performance of a typical office room. The spectrophotometry test on the fabricated TC glass shows a significant modulation ability in near-infrared wavelengths. Based on the measured optical transmittance, daylight behaviors of the glazing were elaborated in terms of visual comfort, color quality of the transmitted light, non-visual daylight availability, and artificial lighting load, using computer simulation methods and numerical calculations. Finally, the paper offers an interactive approach between material development and fabrication methods on one hand, and holistic thermal and daylight analysis of the product on the other hand. This approach optimizes the physical properties of a TC glazing in tradeoff between solar modulation ability, visible transmittance, and color appearance. Highlights: A thermochromic glazing should be fabricated as a tradeoff between Tvis, solar modulation ability, and color appearance. TiO2@W-VO2 glazing modulates the transmission of near infrared radiation in response to temperature variations. The impact of the thermochromic glazing on indoor visual comfort is assessed by DGP and UDI indices. Color quality of the thermochromic glazing is analyzed using Correlated Color Temperature and Color Rendering Indices. Non-visual light efficacy of the thermochromic glazing is assessed using EML and Melanopic Ratio indices.